Ambulatory blood pressure and blood pressure load responses to low sodium intervention in Han Chinese population. (3rd October 2015) - Liu, Fangchao; Chen, Panpan; Li, Dianjiang; Yang, Xueli; Huang, Jianfeng; Gu, Dongfeng
Abstract: We aimed to illustrate ambulatory blood pressure monitoring parameters responses to low sodium intake and their differences between salt-sensitive and non-salt-sensitive individuals. A total of 186 participants were included in this analysis. Twenty-four hour, day-time and night-time blood pressure (BP) and BP load decreased during low sodium intervention, especially in salt-sensitive (SS) group. After multivariable adjustment, 24-h systolic BP, diastolic BP, mean arterial pressure and BP load responses to low sodium intervention of SS individuals were more pronounced than those of non–salt-sensitive individuals. Thus, reducing salt intake is potentially needed for the prevention of hypertension, especially in SS individuals.